Plain English handbook : a complete guide to good English - Walsh, J. Martyn (James Martyn), 1877-.; Walsh, Anna Kathleen (New York : Random House/McCormick-Mathers, 1982)
A handbook of rules for English usage and grammar.
Includes index.
Bibliography: p. 200-201.
Keywords: English language -- Grammar -- Handbooks, manuals, etc; English language -- Grammar